Purkinje-cell-specific MeCP2 deficiency leads to motor deficits and autistic-like behavior due to aberrations in PTP1B-TrkB-SK signaling - Fang-Xiao Xu; Xin-Tai Wang; Xin-Yu Cai; Jia-Yu Liu; Jing-Wen Guo; Fan Yang; Wei Chen; Martijn Schonewille; Chris De Zeeuw; Lin Zhou; Ying Shen (Cell Reports, 2023)
Summary: Patients with Rett syndrome suffer from a loss-of-function mutation of the Mecp2 gene, which results in various symptoms including autistic traits and motor deficits. Deletion of Mecp2 in the brain mimics part of these symptoms, but the specific function of methyl-CpG-binding protein 2 (MeCP2) in the cerebellum remains to be elucidated. Here, we demonstrate that Mecp2 deletion in Purkinje cells (PCs) reduces their intrinsic excitability through a signaling pathway comprising the small-conductance calcium-activated potassium channel PTP1B and TrkB, the receptor of brain-derived neurotrophic factor. Aberration of this cascade, in turn, leads to autistic-like behaviors as well as reduced vestibulocerebellar motor learning. Interestingly, increasing activity of TrkB in PCs is sufficient to rescue PC dysfunction and abnormal motor and non-motor behaviors caused by Mecp2 deficiency. Our findings highlight how PC dysfunction may contribute to Rett syndrome, providing insight into the underlying mechanism and paving the way for rational therapeutic designs.